PENGARUH PERSONAL BRANDING TERHADAP MINAT BELI KONSUMEN (Survei pada followers Social Media YouTube @GadgetIn) - Suprimansyah, Reza; Yusuf, Ramayani (LPPM Politeknik Pajajaran ICB, 2023)
This study aims to evaluate the effect of personal branding on consumer buying interest in followers of YouTube social media @GadgetIn.@GadgetIn is one of the leading YouTube channels in Indonesia that focuses on gadget reviews and reviews and technology-related topics. The survey method was used to collect data from 100 respondents who are students of Garut University. The data were analyzed using simple linear regression techniques with a descriptive quantitative approach with the help of SPSS software. The results showed that personal branding consisting of personal image, trust, and loyalty had a positive and significant effect on purchase intention. The implication of this research is the importance of personal branding in influencing consumer behavior towards consumer buying interest and the importance of implementing effective personal branding for influencers on social media.